2019
DOI: 10.19173/irrodl.v20i1.4012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationships of Factors Which Impact on Learner Achievement in Online Learning Environment

Abstract: The purpose of this study is to identify relationships of learners’ achievement goal orientation, self-regulation, test-anxiety, self-efficacy, participation, satisfaction, and achievement in online learning environments in Korea. A total of 1,832 student responses from a Korean cyber university were used to find structural relationships of factors. Causal relationships among various variables are provided as results of this study. Achievement goal orientation –approach, self-regulated learning, test-anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 28 publications
2
30
1
13
Order By: Relevance
“…For example, Yukselturk and Bulut (2007) reported that students’ self‐regulated learning ability (eg, setting learning goals or monitoring their learning process) is a key factor in achieving success in online courses. Similar findings were also documented in recent studies (Im & Kang, 2019). Moreover, self‐regulatory skills (eg, adapting cognitive strategies for learning or reflecting on learning tasks) were found to be significantly related to learners’ engagement (Sun & Rueda, 2012) and information searching behaviors (Cheng, Liang, & Tsai, 2013) when involved in online learning.…”
Section: Introductionsupporting
confidence: 92%
“…For example, Yukselturk and Bulut (2007) reported that students’ self‐regulated learning ability (eg, setting learning goals or monitoring their learning process) is a key factor in achieving success in online courses. Similar findings were also documented in recent studies (Im & Kang, 2019). Moreover, self‐regulatory skills (eg, adapting cognitive strategies for learning or reflecting on learning tasks) were found to be significantly related to learners’ engagement (Sun & Rueda, 2012) and information searching behaviors (Cheng, Liang, & Tsai, 2013) when involved in online learning.…”
Section: Introductionsupporting
confidence: 92%
“…However, PAV goals negatively predicted students' nonposting behavior and perceived learning in online courses. Im and Kang (2019) concluded that only avoidance goals were negatively related to online participation, satisfaction, and achievement.…”
Section: ×2 Achievement Goal Orientation and Online Learningmentioning
confidence: 99%
“…The success of the doctoral student is typically culminated by the completion of the dissertation and the attainment of the doctoral degree. However, a deeper exploration of student success addresses academic achievement; engagement in educationally purposeful activities; satisfaction; acquisition of desired knowledge, skills, and competencies; persistence; attainment of educational objectives; and post-college performance (Im & Kang, 2019;Kuh, Kinzie, Schuh, & Whitt, 2010). While educational "success" has been broadly and often studied, York, Gibson, and Rankin (2015) acknowledged a lack of comprehensive instrumentation for measuring success outside of academic achievements such as grades, GPA, and degree attainment.…”
Section: Student Learning Successmentioning
confidence: 99%